Analisis Sifat Fisis dan Kimia Produk Minyak Kayu Putih di Pasaran Kota Ambon - Maail, Rohny S.; Purimahua, Vence (MAKILA, 2020)
This study analyzes the physical and chemical characteristics of eucalyptus oil products in the Ambon city market. Eucalyptus oil stamped Merpati Putih/MP to determine the quality grade of MP eucalyptus oil. The MP quality grade is based on the chemical component content level of 1,8-cineole. Furthermore, according to results of the testing on the physics properties of some parameters as required at SNI 3954-2014 about Eucalyptus (Cajuput) Oil standard, and the analysis of chemical components through GC-MS apparatus, the results shows that the MP Cajuput oil has the properties of physics that meet the required standards, among others: the specific gravity (BJ) of 0917, light green-colored towards clear, smelling as typical cajuput oil (original), the refractive indexes at ambient was about 1.469; there was no mixing with other oils (clear) and the absence of fatty oil with an optical rotation value at (-) 0, 33o, respectively. However, the results of the analysis of chemical components by GC-MS proved that the quality of the MP Cajuput oil at the first quality class was based on SNI 3954-2014 due to contains 1.8-cineole whose it value was within the standard ranges of 50 to < 55%, which is 52.51%